2007
DOI: 10.1016/j.amjhyper.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased Human Urotensin II Levels Are Correlated With Carotid Atherosclerosis in Essential Hypertension

Abstract: Our results suggest that increased levels of U-II may play a crucial role in the development of carotid atherosclerosis in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 30 publications
5
49
1
5
Order By: Relevance
“…In our present and previous studies 15,31) , plasma IR-U levels showed a closely positive correlation with carotid maximum IMT as well as BP, suggesting that U may become a reliable biomarker for atherosclerosis. Importantly, it is the first report that both increased plasma IR-U levels and carotid atherosclerosis showed a significantly independent association with VaD.…”
Section: Vsmc Mø Møsupporting
confidence: 80%
See 1 more Smart Citation
“…In our present and previous studies 15,31) , plasma IR-U levels showed a closely positive correlation with carotid maximum IMT as well as BP, suggesting that U may become a reliable biomarker for atherosclerosis. Importantly, it is the first report that both increased plasma IR-U levels and carotid atherosclerosis showed a significantly independent association with VaD.…”
Section: Vsmc Mø Møsupporting
confidence: 80%
“…U in circulating blood is produced mainly by the cardiovascular system, liver, and kidneys 14) . Plasma levels of U are increased in vascular endothelial dysfunction-related diseases, such as hypertension, ischemic heart disease, congestive heart failure, diabetes mellitus, and renal failure, and are positively correlated with systolic blood pressure (BP) and severity of atherosclerosis [14][15][16] . U (molecular weight: 1388) is regarded as a biomarker for atherosclerosis and vascular disease 14) ; however, the association between U and VaD is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The upper normal limit of IMT was 1.0 mm, and the lesions with a focal IMTX1.1 mm were defined as plaques. 10 The plaque score was calculated by summing all plaque thickness measurements in both carotid arteries. The severity of plaque score was graded as follows: none, 0; mild, 1.1-5; moderate, 5.1-10; and severe, X10.1.…”
Section: Carotid Ultrasound Investigationmentioning
confidence: 99%
“…The severity of plaque score was graded as follows: none, 0; mild, 1.1-5; moderate, 5.1-10; and severe, X10.1. 10 Carotid artery elastic parameters Internal diameter measurements were made by continuous tracing of the intima-lumen interfaces of the near and far walls. According to the Atherosclerosis Risk in Communities study protocol and Tomiyama's studies, [11][12][13] carotid strain was assessed as DD Â 100/Dd, where DD and Dd represent pulsatile distension and end-diastolic diameter, respectively.…”
Section: Carotid Ultrasound Investigationmentioning
confidence: 99%
“…ÜT 2 ekspresyonu aynı zamanda aterosklorotik plaklarda vaskü-ler düz kas hücre proliferasyonunu stimule edebilir, daha da fazlası ÜT 2 lokal olarak koroner vazokonstriksiyona neden olabilir ve myokard iskemisini attırabilir [71]. Aterosklorozla ile ilgili yapılan deneysel çalışmalara baktığımız-da ise; Suguro ve arkadaşları [72] yaptığı bir çalışmada hipertansif hastalarda artan ÜT 2 seviyelerinin karotid aterosklerozunun gelişmesinde çok önemli bir rol oynadığını göstermişlerdir. Yine Suguro ve arkadaşları yaptığı bir başka çalışmada [73] artmış plazma ÜT 2 seviyesinin diyabetik retinopati ve karotid aterosklerozunun progresyonu ile ilişkili olduğunu göstermişlerdir.…”
Section: Aterosklerozunclassified